Melatonin: a promising neuroprotective agent for cerebral ischemia-reperfusion injury - Tozihi, Majid; Shademan, Behrouz; Yousefi, Hadi; Avci, Cigir Biray; Nourazarian, Alireza; Dehghan, Gholamreza (Frontiers in Aging Neuroscience, 2023)
Cerebral ischemia-reperfusion (CIR) injury is initiated by the generation of reactive oxygen species (ROS), which leads to the oxidation of cellular proteins, DNA, and lipids as an initial event. The reperfusion process impairs critical cascades that support cell survival, including mitochondrial biogenesis and antioxidant enzyme activity. Failure to activate prosurvival signals may result in increased neuronal cell death and exacerbation of CIR damage. Melatonin, a hormone produced naturally in the body, has high concentrations in both the cerebrospinal fluid and the brain. However, melatonin production declines significantly with age, which may contribute to the development of age-related neurological disorders due to reduced levels. By activating various signaling pathways, melatonin can affect multiple aspects of human health due to its diverse range of activities. Therefore, understanding the underlying intracellular and molecular mechanisms is crucial before investigating the neuroprotective effects of melatonin in cerebral ischemia-reperfusion injury.